1994
DOI: 10.1590/s0102-311x1994000200008
|View full text |Cite
|
Sign up to set email alerts
|

Associação da perda auditiva induzida pelo ruído com o tempo acumulado de trabalho entre motoristas e cobradores

Abstract: Through regression analysis the relationship between noise-induced hearing loss and variables "total cumulative working time", "arterial blood pressure" and "age" was examined. The study was carried out among 278 bus drivers and ticket takers, users of an occupational health center in Campinas, São Paulo State (Brazil). The main results were a positive association between hearing loss and cumulative working time, as well as an interaction between this variable and the bus workers' age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
5
0
6
Order By: Relevance
“…The lack of association between the frequency bands with intense noise levels and the hearing damage frequency found in the present investigation also justify the findings from a research paper which discussed the prevalence of NIHL in bus drivers. 5 It is believed that the noise transmitted by bus engines is in a lower frequency when compared to industrial noises, even then, we see that bus drives, despite being exposed to a different noise spectrum, have hearing losses which are similar to those from industry workers, primarily affecting the high frequencies of the audiogram.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The lack of association between the frequency bands with intense noise levels and the hearing damage frequency found in the present investigation also justify the findings from a research paper which discussed the prevalence of NIHL in bus drivers. 5 It is believed that the noise transmitted by bus engines is in a lower frequency when compared to industrial noises, even then, we see that bus drives, despite being exposed to a different noise spectrum, have hearing losses which are similar to those from industry workers, primarily affecting the high frequencies of the audiogram.…”
Section: Discussionmentioning
confidence: 65%
“…In the study carried out with bus drivers in Campinas, they found a positive association between NIHL and accumulated duration of noise exposure. 5 According to the World Health Organization, the excessive exposure to noise can cause other health problems, such as auditory stress under exposures of 55 dB; physical reaction such as blood pressure raise, heart rhythm and muscle contractions; the increase in adrenaline production and other hormones; irritability; stress; insomnia and anxiety. 6 Epidemiologic studies reveal that occupational hearing problems affect more frequently workers of the following occupations: steel workers, mechanics, graph, textile, chemist/petrochemist, transportation and those in the food and beverage industry, industries with high noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos como o de Cordeiro et al 21 , já evidenciaram associações positivas entre a perda auditiva e o tempo acumulado de trabalho, bem como a existência de uma interação entre essa variável e a idade. Todavia, vale ressaltar que a importância da exposição ao ruído nesta associação deve-se ao fato de que poder-se-ia esperar uma distribuição igual das faixas etárias entre os trabalhadores com ou sem perda auditiva, o que não houve, sendo maior e altamente significativa naqueles com perda auditiva.…”
Section: Resultsunclassified
“…Estudos realizados com motoristas de ônibus demonstraram a prevalência de PAIR variando entre 32% e 62,8% (8)(9)(10)(11)(12)(13)(14)(15) . A idade e o tempo de serviço exerceram influência sobre a ocorrência desta alteração; constatou-se que quanto maior o tempo de exposição, maior o número de frequências atingidas (9,10) . Observou-se ainda que houve predominância de audiogramas sugestivos de PAIR para os motoristas com tempo de exposição superior a seis anos (12,13,16) .…”
Section: Introductionunclassified